KERJASAMA NCB INTERPOL INDONESIA DALAM MEMBANTU NCB INTERPOL KOREA SELATAN TERKAIT EKSTRADISI LIM THOW KAI DAN ALEX GO DALAM KASUS PENYELUDUPAN NARKOTIKA TAHUN 2017-2019 - Risty Khairiendra, (2023)
The International Criminal Police Organization (ICPO) or INTERPOL is an international organization that fights transnational crimes. INTERPOL has a global communication system called I-24/7, which effectively handles transnational crimes through notifications. Red notice is one of INTERPOL's notifications that plays a crucial role and is issued to all NCB-INTERPOL to all member countries searching the international wanted list. In today's world, many crimes occur in more than one country's jurisdictions which is a special focus for INTERPOL. One case that INTERPOL Indonesia currently handled was the extradition of Lim Thow Kai and Alex Go narcotics smuggling to South Korea. The quick action of NCB-INTERPOL Indonesia proved its commitment to eradicating international crime. This article used the qualitative research method, which was supported with reliable data and sources from NCB-INTERPOL Indonesia and reviewed using the supporting international theory concept of bilateral cooperation. The INTERPOL Indonesia cooperation system also supports international relations instruments and laws that apply to its member countries, such as implementing mutual legal assistance and extradition. The effectiveness of the role and pattern of INTERPOL Indonesia's cooperation is depicted in how they handle extradition requests by South Korea's Interpol for foreign citizens on behalf of Lim Thow Kai and Alex Go, the result is in the form of an article that describes the collaboration of NCB Interpol Indonesia and NCB Interpol South Korea in the extradition of perpetrators of narcotics crimes in South Korea.